2017
DOI: 10.1108/ijlm-04-2014-0066
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain management skills to sense and seize opportunities

Abstract: Purpose The purpose of this paper is to investigate the supply chain management (SCM) skills that support the sensing and seizing of opportunities in a changing business environment. Design/methodology/approach Based on the previous literature on the T-shaped model of SCM skills, data were collected through a mail survey among Australian business executives. The resultant skill sets are grouped along factors that support the sensing vs seizing of opportunities. Findings Interestingly from an SCM perspectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 64 publications
3
51
0
3
Order By: Relevance
“…It emerged that individuals also deployed boundary activities to gain support from within and from outside their organization for their domain of expertize (engaging boundary work) and to close themselves off from other expertize domains (disengaging boundary work). This emerging finding is consistent with the findings of Tatham, Wu, Kovács, and Butcher () who conclude that general management skills like relational and interpersonal capabilities are more important in complex environments than technical skills obtained through education and training.…”
Section: Discussionsupporting
confidence: 91%
“…It emerged that individuals also deployed boundary activities to gain support from within and from outside their organization for their domain of expertize (engaging boundary work) and to close themselves off from other expertize domains (disengaging boundary work). This emerging finding is consistent with the findings of Tatham, Wu, Kovács, and Butcher () who conclude that general management skills like relational and interpersonal capabilities are more important in complex environments than technical skills obtained through education and training.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have shown that SCM has always faced increasing turbulence in the business environment, competing markets, ever‐faster cycle times, and complex supply chains (Makarius and Srinivasan 2017; Tatham et al 2017). Considering these circumstances and the cross‐disciplinary character of SCM (Derwik and Hellström 2017), our findings support available studies in the sense that people in the SCM field are also subject to intense learning adaptability (Kotzab et al 2018; Wrobel‐Lachowska 2018).…”
Section: Discussion Of Topic Clustersmentioning
confidence: 99%
“…As an essential reason for the decisive influence of people, van Hoek et al (2002) emphasize the richness of the necessary capabilities to do the job properly, especially in the field of SCM. Accordingly, over the years a significant amount of research has explored the skills and competency requirements necessary for SCM talents (Gammelgaard and Larson 2001;Gibson and Cook 2001;Myers et al 2004;Mangan and Christopher 2005;Murphy and Poist 2006;Richey et al 2006;Derwik et al 2016;Goffnett et al 2016;Derwik and Hellstr€ om 2017;Makarius and Srinivasan 2017;Tatham et al 2017;Fl€ othmann et al 2018;Kotzab et al 2018).…”
Section: Literature Review and Theorymentioning
confidence: 99%
“…Tatham et al ( 2017 ) refer to skills rather than competences and categorize those as problem solving (PSS), general management (GMS), interpersonal (IPS), and functional (FS). They conclude that, in the quest for competitive advantage, PSS skills are needed to sense, and GMS and IPS skills to seize opportunities.…”
Section: The Theoretical Framework and The Propositionsmentioning
confidence: 99%